Implikatur dalam Percakapan Tertulis Bahasa Inggris SMA - Sudirman Sudirman (Aksara: Jurnal Bahasa dan Sastra, 2018)
This article presents a study of implicature in written English conversation. Up to the present, there has not been a research carried out on written English conversation, while there are many conversation units written in Senior High School (SMA) Sdudents` book. This study, therefore, was aimed at describing the types of implicature in written conversation in SMA students` book. The source of data was accordingly taken from a conversation unit written in SMA students book entitled English Alive Senior High School published by Yudistira. From this book, one topic of conversation was taken then analized using pragmatical conversational schame to find the types of implicature implied in it. The result of the analysis showed that there were fifteen implicature types used by conversational locuters. The fifteen types of implicatures were mainly lingual in form of word, phrase, clause, and sentence. DOI: http://dx.doi.org/10.23960/aksara/v19i1.pp37-53